Sequencing of new beauverolides by high-performance liquid chromatography and mass spectrometry - Kuzma, M; Jegorov, A; Kacer, P; Havlícek, V (Journal of mass spectrometry, 2001)
Mass spectrometry (MS) and tandem mass spectrometry (MS(n)) were used for the identification of beauverolides in the fermentation broth of Beauveria bassiana and for evaluation of the purified fraction obtained by sublimation of beauverolides. Besides being a new efficient route for purification of beauverolides, sublimation provided an enrichment of new minor lipophilic beauverolides of lower molecular weight from the original complex mycelial extract. The product ion collision-induced dissociation (CID) spectra obtained on an ion trap (electrospray ionization), the in-source CID mass spectra on a sector instrument (atmospheric-pressure chemical ionization) and the post-source decay matrix-assisted laser desorption/ionization mass spectra of beauverolides were compared and evaluated. All MS(n) experiments started with singly charged precursor ions. The following two new representatives of this group of compounds were identified by high-performance liquid chromatography and MS (HPLC/MS): cyclo-(3-hydroxy-4-methyloctanoyl-valyl-alanyl-leucyl) and cyclo-(3-hydroxy-4-methyloctanoyl-tyrosyl-alanyl-leucyl). Individual structures were confirmed by preparative isolation and nuclear magnetic resonance spectroscopy. The structure of a third novel and minor beauverolide was tentatively assigned by HPLC/MS only as cyclo-(3-hydroxy-4-methyldecanoyl-valyl-alanyl-Lxx), Lxx = leucyl, isoleucyl, or allo-isoleucyl.
Keywords: Peptides, Cyclic; Ascomycota; depsipeptidy; sekvenční analýza; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Depsipeptides; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Chromatography, High Pressure Liquid; Amino Acids; cyklické peptidy; Mass Spectrometry; aminokyseliny; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; Sequence Analysis